PHILOSOPHY AND SPECIAL SCIENCES - Eugenijus Meškauskas (Problemos)
The problem of the relationship of the philosophy with the special sciences arose in the modern time. However this problem has rich prehistory related to the differences between conceptions of nature manifesting itself already in the ancient philosophy. In the empiricist tradition philosophy is considered as the methodological factor external with respect to natural science. This problem includes too the different ontological interpretations of natural scientific data connected with the unavoidable conventionality of the outlooks on the epistemic status of the philosophy itself.